Revolution is the way you eat: exemplification among left radical activists in Denmark and in anthropology. (May 2015) - Krøijer, Stine; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> In anthropology, examples have always been an integral part of the investigation of the social life of people. Sometimes they simply work as a poor illustration of an author's general or existing theoretical ideas, but on other occasions they are conducive to setting new thoughts in motion. This paper explores the role of the example among left radical activists in the context of the Climate Summit (COP 15) protests in Copenhagen and a trip to forage for discarded food in a supermarket container in order to feed activists. I argue that examples make up a theory of change that evades problematic distinctions between the particular and universal, and set new actions in motion on a horizontal plane without relying on a predefined plan or end‐point. The paper points to the ways this may inform the use of examples within the anthropological discipline.